Penerapan Problem Solving Cycle dalam Perencanaan Intervensi Perilaku Kesehatan: Analisis Situasi Berbasis Data Sekunder - Irfan Sazali Nasution; Maya Adella Zuliana; Rika Halimah; Devi Helma Fitri Hasibuan; Nuraini Nuraini; Shinta Aulia Agusta (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Handwashing with soap (HWWS) is one of the simplest, most effective, and cost-efficient behaviors for preventing infectious diseases. However, its practice remains suboptimal at the household level in Indonesia. This research aims to analyze HWWS behavior using community questionnaire data as a basis for developing health promotion strategies through the Problem Solving Cycle (PSC) approach. This descriptive quantitative study was conducted among 50 respondents using a closed-ended questionnaire covering the knowledge, attitude, and practice dimensions of HWWS. The results showed that although respondents had high awareness and positive attitudes toward HWWS, their practices remained inconsistent due to habitual and infrastructural barriers. These findings highlight the need for integrated interventions combining direct education, social media campaigns, and improved access to handwashing facilities. This study contributes to evidence-based, participatory, and contextually adapted health promotion strategies aimed at achieving sustainable behavioral change.